1990
DOI: 10.1029/jb095ib05p06685
|View full text |Cite
|
Sign up to set email alerts
|

Age estimates and uplift rates for Late Pleistocene marine terraces: Southern Oregon portion of the Cascadia Forearc

Abstract: Marine terraces are prominent landforms along the southern Oregon coast, which forms part of the forearc region of the Cascadia subduction zone. Interest in the Cascadia subduction zone has increased because recent investigations have suggested that slip along plates at certain types of convergent margins is characteristically accompanied by large earthquakes. In addition, other investigations have suggested that convergent margins can be broadly classified by the magnitude of their uplift rates. With these hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 51 publications
2
72
0
Order By: Relevance
“…Amino acid ratios in the bivalve Saxidomus reported by Kennedy et al (1982) suggested that the Cape Blanco terrace could be younger than the Whisky Run terrace at Coquille Point. Later amino acid and oxygen isotope studies, also on Saxidomus valves, suggested that the two terraces could be correlative (Muhs et al, 1990). Correlation of the Cape Blanco and Whisky Run terraces is also supported by soils data (Bockheim et al, 1992;Kelsey and Bockheim, 1994).…”
Section: Southern Oregonmentioning
confidence: 50%
See 2 more Smart Citations
“…Amino acid ratios in the bivalve Saxidomus reported by Kennedy et al (1982) suggested that the Cape Blanco terrace could be younger than the Whisky Run terrace at Coquille Point. Later amino acid and oxygen isotope studies, also on Saxidomus valves, suggested that the two terraces could be correlative (Muhs et al, 1990). Correlation of the Cape Blanco and Whisky Run terraces is also supported by soils data (Bockheim et al, 1992;Kelsey and Bockheim, 1994).…”
Section: Southern Oregonmentioning
confidence: 50%
“…Addicott (1964Addicott ( , 1966, Zullo (1969), and Kennedy (1978) studied fossils from the Whisky Run and Cape Blanco terraces. In a previous study, a coral from the Whisky Run terrace at Coquille Point yielded an alpha-spectrometric U-series age of 80,000 yr BP (Muhs et al, 1990). Amino acid ratios in the bivalve Saxidomus reported by Kennedy et al (1982) suggested that the Cape Blanco terrace could be younger than the Whisky Run terrace at Coquille Point.…”
Section: Southern Oregonmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cascadia subduction zone also seems to fit the model reasonably well, as it has an intermediate type of subduction zone geometry (Jarrard, 1986) and the data presented here show variable, but generally intermediate uplift rates when compared to the two extremes of the Ryukyu Islands. Nevertheless, other subduction zones do not seem to fit the model very well (see review in Muhs et al (1990)). For example, the uplift rate in a coastal area of northcentral Chile that can be categorized (as its name implies) as a "Chilean" type of subduction zone has, in fact, a rather modest late Quaternary uplift rate of 0.16 m/ka (Leonard and Wehmiller, 1992).…”
Section: Comparison Of Channel Islands Uplift Rates With Other Localimentioning
confidence: 99%
“…Paleo-sea levels, relative to present, used for uplift rate calculations are þ6 m (~120 ka), À11 m (~80 ka), and À62 m (~49 ka), derived from data in Muhs et al (2012). Abbreviations and sources of data, south to north: CP, Cabo Pulmo (Muhs et al, 2002a); LP, La Paz (Sirkin et al, 1990); BH, Bahía Magdalena (Omura et al, 1979); IC, Isla Coronados and PC, Punta Chivato (Johnson et al, 2007; see also Table 2); MU, Mulege (Ashby et al, 1987); BT, Bahía de Tortugas (Emerson et al, 1981); PB, Punta Banda (Rockwell et al, 1989;Muhs et al, 2002a); PL, Point Loma (Kern, 1977;Muhs et al, 2002a); SCI, San Clemente Island (Muhs et al, 2002a; NB, Newport Bay (Grant et al, 1999); SNI, San Nicolas Island ; PV, Palos Verdes Hills (Muhs et al, 2006); NCI, Northern Channel Islands (this study); V, Ventura Kennedy et al, 1982;Wehmiller, 1982); IV, Isla Vista (Gurrola et al, 2014; see also Table 2); SB, Shell Beach (Stein et al, 1991;Hanson et al, 1994); PSL, Point San Luis (Hanson et al, 1994;Muhs et al, 1994); C, Cayucos (Stein et al, 1991;Muhs et al, 2002a); AN, Año Nuevo (Muhs et al, 2006); PA, Point Arena (Muhs et al, 2006); PD, Point Delgada (McLaughlin et al, 1983a(McLaughlin et al, , 1983bMerritts and Bull, 1989); CC, Crescent City (Kennedy et al, 1982;Polenz and Kelsey, 1999); CB, Cape Blanco (Kelsey, 1990;Muhs et al, 1990); B, Bandon (McInelly and Kelsey, 1990;…”
Section: Comparison Of Channel Islands Uplift Rates With Other Localimentioning
confidence: 99%